2001
DOI: 10.1016/s1044-0305(00)00195-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of multiply charged negative ions for hirudin (54–65), fibrinopeptide B, and insulin A (oxidized)

Abstract: Collision-induced dissociation (CID) was performed on multiply deprotonated ions from three commercial peptides: hirudin (54-65), fibrinopeptide B, and oxidized insulin chain A. Ions were produced by electrospray ionization in a Fourier transform ion cyclotron resonance mass spectrometer. Each of these peptides contains multiple acidic residues, which makes them very difficult to ionize in the positive mode. However, the peptides deprotonate readily making negative ion studies a viable alternative. The CID spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…Abstraction of the C ␣ -hydrogen results in formation of a peptide enolate at Cys residues, which can subsequently cleave to yield dehydroalanine residue with loss of H 2 S or H 2 S 2 . The use of negative ion mass spectrometry [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for the study of disulfide containing peptide natural products has been established in an extensive series of investigations by Bowie and coworkers [30 -35] and other groups [36 -38]. During the course of recent attempts to fragment the negative ions of disulfide bridged peptides under mass spectrometric conditions, we noted that the cleavage reactions closely resemble those observed during breakage of disulfide bonds under alkaline conditions [39,40].…”
mentioning
confidence: 89%
“…Abstraction of the C ␣ -hydrogen results in formation of a peptide enolate at Cys residues, which can subsequently cleave to yield dehydroalanine residue with loss of H 2 S or H 2 S 2 . The use of negative ion mass spectrometry [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for the study of disulfide containing peptide natural products has been established in an extensive series of investigations by Bowie and coworkers [30 -35] and other groups [36 -38]. During the course of recent attempts to fragment the negative ions of disulfide bridged peptides under mass spectrometric conditions, we noted that the cleavage reactions closely resemble those observed during breakage of disulfide bonds under alkaline conditions [39,40].…”
mentioning
confidence: 89%
“…Penta-alanine also produces a n − and ″b n − , which is typical of oligoalanine peptides in the negative ion mode [41]. Neutral loss peaks common to specific amino acid residues are abundant in the spectra; for example, elimination of H 2 O and CH 2 O from serine [42][43][44][45][46][47][48][49], the guanidino group (HN=C=NH) from arginine [40,49,50], H 2 O from aspartic acid [51][52][53][54], O=C 6 H 4 =CH 2 from tyrosine [54], and CH 3 SH, CH 3 SCH 3 , and CH 2 CH 2 SCH 3 from methionine [55].…”
Section: Resultsmentioning
confidence: 99%
“…In EID, only the c 9 product ion was observed. Formation of c-type product ions is generally observed in negative ion mode CAD [21,29,60]. Some y-and b-type ions, y 4 , b 4 , and b 7 , observed in CAD were absent in EID.…”
Section: Resultsmentioning
confidence: 99%
“…However, utilization of negative ion mode is often desired, given that~50% of naturally occurring proteins are acidic. Peptides containing numerous acidic residues (e.g., glutamic and aspartic acid) may be challenging to detect in positive ion mode [21][22][23]. On the other hand, it has been shown that highly basic peptides can easily form singly deprotonated ions with sufficient intensities for fragmentation experiments [24].…”
Section: Introductionmentioning
confidence: 99%